Relations between Daytime Pre-ejection Period Reactivity and Sleep in Late Childhood - Bagley, Erika J. (2013)
The sympathetic nervous system and children’s sleep serve critical arousal regulation functions. Shortened pre-ejection period, a reliable indirect index of greater sympathetic nervous system activity, has been associated with reduced sleep duration and quality in adults, but limited evidence exists in children regarding associations between pre-ejection period and sleep. We examined relations between pre-ejection period reactivity in response to a lab-based stressor and multiple parameters of actigraphy-based sleep duration and quality in children. The sample included 123 boys and 112 girls (M age = 11.31 years, SD = .63 years). Controlling for body mass index, sex, and pre-ejection period baseline, increased sympathetic nervous system reactivity, indexed by a lower level of pre-ejection period during the challenge than the baseline, was associated with worse sleep quality indicated by lower sleep efficiency, greater sleep activity, and greater long wake episodes. Findings add to a small literature on relations between sympathetic nervous system functioning and children’s sleep, suggesting that poor sleep quality is related to dysregulation of the stress response system.